Os games enquanto jornadas fenomenológicas: a experiência estética semiótica nos jogos digitais - Souza, Aline Antunes de (2017)
This study aims to explore how games may be able to provide their players with meanin experiences. To what extent are qualities such as contemplation, ecstatic chance, habit change, and self-knowledge, tlnough moral and ethical questioning, are also involved in the act of playing? And what kinds of experiences are these aspects capable of creating? The intent is to analyze some of the semiotic elements that are able to bring some explanation about the reasons that make games to exert so much attraction to their users, an attraction that cannot be understood by the simple observation that games are made exclusively for fun. For the investigation, three games were selected, Journey (2012), Portal (2007) and The Walking Dead (2012), to reflect on the possibilities of experience that their joumeys allow. Their semiotic aspects are investigated from C. S. Peirce's Phenomenology, Aesthetics and Semiotics perspectives, in order to find a phenomenological predominance in the immediate interpretant of each one, that is, in their immanent potential to signifr. As a result, tlnee semiotic cartographies of the possibilities of games experiences, inspired by the universal Peircian categories are defined: firstness, secondness and thirdness. As so, this study is mainly based on the Phenomenology, Aesthetics and Semiotics of Charles Sanders Peirce and the works of Lucia Santaella, Priscila Arantes, Mima Feitoza, Cleomar Rocha and Brian Upton